Technology market intermediaries to facilitate external technology exploitation: The case of IP auctions - Frank Tietze (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2008)
Recently the phenomena of external technology exploitation (ETE) has started to attract attention from scholars, businesses and politicians likewise alongside with a growth of the markets for technology. However, the markets for technology are still characterized by inhibiting obstacles that lead to high transaction costs, thus prohibit efficient transactions and result in market failure. Although, on the one hand the presence of obstacles lead to high transaction costs, the large market potential on the other hand provides incentives for technology market intermediaries (TMI) to develop new exploitation models to facilitate ETE transactions by reducing transaction costs. Throughout this paper we address the general research question of whether and how new exploitation models can actually facilitate ETE. To address this question, in a first step we generate insights into TMIs acting on the markets for technology and derived a conceptual basis for a further understanding of TMIs. Having carried out a detailed review of the literature, we develop a theory based typology for six TMI archetypes. Throughout this exercise we gain insights into the variety of different functions TMIs have on the markets for technology and various new ways how TMIs try to facilitate ETE transactions. Throughout the second part of this paper, we focus on IP auctions as one particular business model of the archetype “IP Broker”. We investigate this “young” business model presenting first insights into two qualitative studies. In a first step we derive a generic IP auction process based on a qualitative, empirical analysis of IP auction processes. We then translate these results into a theory based process view and derive a generic IP auction process as a specific type of an ETE process. Having thus generated a close understanding of the transaction process, we presented results from four cases of successful transactions, i.e. where patents were sold for particular high prices from two SMEs and two MNCs. The case studies are analyzed according to four main aspects including characteristics of the companies that exploited patented technologies (including motives and selection processes), the patented technology as such, the organization of the transaction and the companies' perceptions regarding the success of the transactions.
Keywords: 650